Aedes aegypti e fauna associada em área rural de Manaus, na Amazônia brasileira Aedes aegypti and associated fauna in the rural zone of Manaus, in the Brazilian Amazon - Maria Graças Vale Barbosa; Nelson Ferreira Fé; Rossicleide Dias Barbosa de Jesus; Iria Cabral Rodriguez; Wuelton Marcelo Monteiro; Maria Paula Gomes Mourão; Jorge Augusto de Oliveira Guerra (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
Após detectar larvas de Aedes aegypti em área rural de Manaus, realizou-se durante dois anos consecutivos um trabalho de notificação da ocorrência dessa espécie naquela área, através da vigilância entomológica, ferramenta que representa um importante papel entre as medidas preventivas contra doenças de transmissão por insetos em particular as arboviroses. After detecting Aedes aegypti larvae in the rural zone of Manaus, entomological surveillance was carried out over two consecutive years in order to notify occurrences of this species in that area. The tool of entomological surveillance has an important role among the preventive measures against diseases transmitted by insects, particularly arbovirosis.